1. ## Group Homomorphisms

Let $\varphi :G\rightarrow H$ be a group homomorphism. Show that $\varphi[G]$ is abelian if and only if for all $x,y\in G,$ we have $xyx^{-1}y^{-1}\in Ker\left ( \varphi \right )$

2. ## Re: Group Homomorphisms

let [tex]\varphi (G) [tex] be abelian want for [tex]x,y \in G [tex] we have $xyx^{-1}y^{-1}\in Ker(\varphi)$
you should know that
$Ker(\varphi) = \{ g \in G \mid \varphi(g) = e_H\}$
so if we prove that $\varphi (xyx^{-1}y^{-1} ) = e_H$
we are finished $\varphi$ is homo which means $\varphi (ab)= \varphi (a) \varphi(b)$ and $\varphi(a^{-1}) = ( \varphi(a))^{-1}$

not the converse direction for all $x,y \in G$ we have $xyx^{-1}y^{-1} \in Ker(\varphi)$
want $\varphi(G)$ abelian
let $a,b \in \varphi (G) \Rightarrow \varphi^{-1} (a) , \varphi^{-1}(b) \in G$

$\varphi^{-1} (a)\varphi^{-1}(b) (\varphi^{-1}(a))^{-1} (\varphi^{-1}(b))^{-1} \in Ker(\varphi)$

$\varphi [\varphi^{-1} (a)\varphi^{-1}(b) (\varphi^{-1}(a))^{-1} (\varphi^{-1}(b))^{-1}] = e_H$

but it is homo

$\varphi [\varphi^{-1} (a)\varphi^{-1}(b) (\varphi^{-1}(a^{-1})) (\varphi^{-1}(b^{-1}))] = e_H$

$aba^{-1}b^{-1} = e_H \Rightarrow ab = ba$
the proof ends

3. ## Re: Group Homomorphisms

this is just the same thing as Amer said:

suppose that $\varphi(G)$ is abelian. then for any x,y in G:

$\varphi(xyx^{-1}y^{-1}) = \varphi(x)\varphi(y)\varphi(x^{-1})\varphi(y^{-1})$ (since φ is a homomorphism)

$=\varphi(x)\varphi(y)(\varphi(x))^{-1}(\varphi(y))^{-1}$ (again, since φ is a homomorphism)

$= \varphi(x)(\varphi(x))^{-1}\varphi(y)(\varphi(y))^{-1}$ (since φ(G) is abelian).

$= e_He_H = e_H$ showing that $xyx^{-1}y^{-1} \in ker(\varphi)$

on the other hand suppose that $xyx^{-1}y^{-1} \in ker(\varphi)$ for all x,y in G.

for any g,h in φ(G), we have φ(x) = g and φ(y) = h, for SOME x,y in G (because φ is onto φ(G)). but we know that $xyx^{-1}y^{-1} \in ker(\varphi)$,

so $\varphi(xyx^{-1}y^{-1}) = e_H$. but:

$\varphi(xyx^{-1}y^{-1}) = \varphi(x)\varphi(y)(\varphi(x))^{-1}(\varphi(y))^{-1}$

$= ghg^{-1}h^{-1} = e_H$, which quickly gives:

$gh = hg$

the quantity $xyx^{-1}y^{-1}$ is called the commutator of x and y, and is written [x,y]. and here's a sneak peek of what lies ahead:

the subgroup of G generated by all the commutators, is called the commutator subgroup [G,G] (or sometimes G'). and what you (we?) have just proved is that
G/[G,G] is an abelian group (think about this for a second until it dawns on you what i am saying is true).

well, we've almost proved that. we haven't yet shown that [G,G] is normal in G, but it is, and if φ:G-->H is a homomorphism, and H is abelian, then ker(φ) contains [G,G]. [G,G] measures how "non-abelian" G is, in a natural way (the center of G,Z(G), does the same thing, but in a way that is "not natural").

if we write $a^g$ for $gag^{-1}$, try proving that:

$[a,b]^g = [a^g,b^g]$. this shows [G,G] is normal (why?).